2018
DOI: 10.4172/2572-4916.1000188
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically Assisted Fixation of the Tibial Plateau Fractures

Abstract: Objectives: To consolidate the current literature and find the evidence of any advantages of the use of the above mentioned techniques and also to emphasize the need for well-designed studies to evaluate long-and short-term function and risk of posttraumatic osteoarthritis in arthroscopically-assisted treated patients. Background:The role of arthroscopy in the fixation of tibial plateau fractures has been advocated in the literature in the last decades. A number of papers have been published regarding Arthrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The least frequent types were double plates & screws in 1 patient and lateral locked plate in 1 patient [5.0% for each] Table (2). Mean time of union was 11 weeks with standard deviation of 2 weeks Table ( 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The least frequent types were double plates & screws in 1 patient and lateral locked plate in 1 patient [5.0% for each] Table (2). Mean time of union was 11 weeks with standard deviation of 2 weeks Table ( 3).…”
Section: Resultsmentioning
confidence: 99%
“…Open reduction and internal fixation [ORIF] is the standard treatment option. Several complications may arise from ORIF, such as wound complications and infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the other study by Thanappan et al, (2019) (19) aimed to A follow-up study of 10 patients with displaced complicated tibial plateau fractures indicated 90% had acceptable or outstanding functional outcomes after column-specific repair. All the fractures in their research also healed in around three to four months.…”
Section: Discussionmentioning
confidence: 99%